2015
DOI: 10.3390/toxins7030997
|View full text |Cite
|
Sign up to set email alerts
|

Further Evidence for Staphylococcal Food Poisoning Outbreaks Caused by egc-Encoded Enterotoxins

Abstract: Staphylococcal food poisoning represents the most prevalent foodborne intoxication worldwide. It is caused by oral intake of enterotoxins preformed by Staphylococcus aureus in food. The relevance of newly described enterotoxins in outbreaks of staphylococcal food poisoning is controversially discussed. Although the staphylococcal enterotoxins SEG, SEI, SEM, SEN, and SEO elicit emesis in a monkey feeding assay, there has been no conclusive proof of their emetic activity in humans. In this study, we provide furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(90 citation statements)
references
References 31 publications
7
72
0
6
Order By: Relevance
“…On the other hand, the prevalence of genes of egc cluster, and the other genes was similar in human (mean, 1.19), animal (1.28), and foodborne origin isolates (1.28) (P N 0.05). Previous studies have showed that strains carried novel SE or SE-like genes could cause SFPs (McLauchlin et al, 2000;Argudín et al, 2010;Johler et al, 2015), so the isolates harboring these genes were new potential hazards to food safety.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the prevalence of genes of egc cluster, and the other genes was similar in human (mean, 1.19), animal (1.28), and foodborne origin isolates (1.28) (P N 0.05). Previous studies have showed that strains carried novel SE or SE-like genes could cause SFPs (McLauchlin et al, 2000;Argudín et al, 2010;Johler et al, 2015), so the isolates harboring these genes were new potential hazards to food safety.…”
Section: Discussionmentioning
confidence: 99%
“…Most of that difference may be attributed to the use of an endogenous starter culture that was contaminated with the same microorganism in the same season (P < 0.05; Table 2). The presence of this bacterium in counts higher than 10 4 cfu/g in all analyzed cheeses from both seasons is alarming; it may produce enterotoxins and cause food poisoning (Johler et al, 2015).…”
Section: Microbiological and Physicochemical Quality Of Fresh Minas Amentioning
confidence: 99%
“…), urinary infections [54,55], and respiratory infections (e.g. rhinosinusitis [56,57], and food poisoning [58][59][60]. It may be also involved in systemic infections [61,62].…”
Section: Staphylococcus Aureus Germs Are Often Involved In Local Imentioning
confidence: 99%